Preliminary Study on Worldviews - Sartini Sartini; Heddy Shri Ahimsa-Putra (Humaniora, 2017)
Worldviews are an important part of human life because they illustrate the ways people think and act. This article aims to review studies conducted by scholars, definitions of the term "worldview", and scientists' explorations of worldviews, and to examine how such categories may be applied to capture reality. This study concludes that worldviews have been the focus of intensive studies since the 1980s. Many scientists have defined the concept of "worldview" and attempted to explain its dynamics. Studies of worldviews can be grouped into several paradigms. Because of the extent of the study area, theoretically worldviews can be classified into several categories based on, for example, views of self and others, time, space, relationships, and causation. In reality, the worldview of a society can be seen in how members of the society live in relation to God, nature, people, and the environment. In examining the worldviews held in social reality, the specific categories mapped by scholars must be made congruent with the realities in the field, because sometimes these categories are interrelated and difficult to understand separately.